Art nature dialogues : interviews with environmental artists - Grande, John K. (Albany : State University of New York Press, 2004)
"Art Nature Dialogues offers interviews with artists working with, in, and around nature and the environment. The interviews explore art practices, ecological issues, and values as they pertain to the siting of works, the use of materials, and the ethics of artmaking. John K. Grande includes interviews with Hamish Fulton, David Nash, Bob Verschueren, herman de vries, Alan Sonfist, Nils-Udo, Michael Singer, Patrick Dougherty, Ursula von Rydingsvard, and others."--Jacket
Real living art / David Nash -- Yardworking / Patrick Dougherty -- Ecohabitat / Gilles Bruni and Marc Barbarit -- Ephemeral public art / Jerilea Zempel -- In nature's eyes / Alfio Bonanno -- Mechanical botanical / Doug Buis -- Designing with nature / Michael Singer -- The vegetal (and mineral) world(s) of / Bob Verschueren -- Nature vision / Nils-Udo -- Riverwork / Mario Reis -- Cosmological shadows / Bill Vazan -- No walk no work! / Hamish Fulton -- The spike / Egil Martin Kurdøl -- Culture nature catalyst / Betty Beaumont -- Natural/cultural / Alan Sonfist -- Ship of life / Peter von Tiesenhausen -- Earth in context / Reinhard Reitzenstein -- Earthbound mystery / Ursula von Rydingsvard -- Healing garden / Mike MacDonald -- chance & change / herman de vries -- The heart of the matter / Chris Drury.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Environment (Art); Earthworks (Art); Artists -- Interviews; Environnement (Art); Land art; Artistes -- Entretiens; Art -- Intégration à l'architecture.; earthworks (sculpture); environmental art; ART -- History; Artists; Earthworks (Art); Environment (Art); Art environnemental; Artiste; Land art; Interview; interviews; Interviews; Interviews; Interview (Descripteur de forme); Interviews